2010
DOI: 10.2147/ijn.s13244
|View full text |Cite|
|
Sign up to set email alerts
|

Concentration-dependent toxicity of iron oxide nanoparticles mediated by increased oxidative stress

Abstract: Iron oxide nanoparticles with unique magnetic properties have a high potential for use in several biomedical, bioengineering and in vivo applications, including tissue repair, magnetic resonance imaging, immunoassay, drug delivery, detoxification of biologic fluids, cell sorting, and hyperthermia. Although various surface modifications are being done for making these nonbiodegradable nanoparticles more biocompatible, their toxic potential is still a major concern. The current in vitro study of the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
265
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(286 citation statements)
references
References 36 publications
(18 reference statements)
17
265
0
4
Order By: Relevance
“…Exposure to SPIONs and a Magnetic Force Does Not Lead to Cytotoxicity of the BCECs. SPIONs have been shown to induce oxidative stress, 12 and therefore, we wanted to test the cell viability within the time frame of this study. It is also known that cells of different origin react differently upon exposure to SPIONs; this phenomenon is called the "cell vision".…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to SPIONs and a Magnetic Force Does Not Lead to Cytotoxicity of the BCECs. SPIONs have been shown to induce oxidative stress, 12 and therefore, we wanted to test the cell viability within the time frame of this study. It is also known that cells of different origin react differently upon exposure to SPIONs; this phenomenon is called the "cell vision".…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 Typically, the SPIONs have a mean diameter of 50−100 nm, 11 and their iron oxide core exerts low toxicity, as it is gradually degraded to Fe 3+ in the body and enters the pool of body iron; 11 e.g., SPIONs induce oxidative stress only in murine macrophage (J774) cells at doses higher than 100 μg/mL. 12 The magnetic core of SPIONs can be coated with lipophilic fluorescent dyes for visual detection. Furthermore, the particles can be protected by biocompatible polymeric shell materials like dextran, polysorbate, or starch or coated by phospholipids or polyethylene glycol (PEG) to prolong their presence within the circulation because of a lower level of recognition of the particles by the reticulo endothelial system.…”
mentioning
confidence: 99%
“…We analyzed the possible cytotoxic effects of DMSA-MNP on NCTC 1469 hepatic cells. As most previous studies of MNP cytotoxicity were conducted at low nanoparticle concentrations, or incubation times potentially too short to determine all possible toxic effects on cultured cells [28], we used iron concentrations up to 0.5 mg/ml, and incubation times up to 72 h.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that toxicity of SPIONs with a mean size of 30 nm coated with Tween 80 surfactant in murine macrophage (J774) cells was found to be due to induction of oxidative stress and subsequent apoptosis. The intracellular ROS generation evaluated by a H 2 DCFDDA assay showed both concentration-and time-dependent, and the enhanced ROS production led to cell injury and death [55].…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%
“…Although some studies have not found the direct correlation between toxicity and ROS production induced by MNPs [49], most studies concluded that nanoparticles can be toxic, not only affecting cells in a direct way, but also indirectly by the induction of excess ROS [54,55]. It is reported that toxicity of SPIONs with a mean size of 30 nm coated with Tween 80 surfactant in murine macrophage (J774) cells was found to be due to induction of oxidative stress and subsequent apoptosis.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%